3xy-x+9y+2=0

Simple and best practice solution for 3xy-x+9y+2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3xy-x+9y+2=0 equation:


Simplifying
3xy + -1x + 9y + 2 = 0

Reorder the terms:
2 + -1x + 3xy + 9y = 0

Solving
2 + -1x + 3xy + 9y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -1x + 3xy + -2 + 9y = 0 + -2

Reorder the terms:
2 + -2 + -1x + 3xy + 9y = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -1x + 3xy + 9y = 0 + -2
-1x + 3xy + 9y = 0 + -2

Combine like terms: 0 + -2 = -2
-1x + 3xy + 9y = -2

Add '-9y' to each side of the equation.
-1x + 3xy + 9y + -9y = -2 + -9y

Combine like terms: 9y + -9y = 0
-1x + 3xy + 0 = -2 + -9y
-1x + 3xy = -2 + -9y

Reorder the terms:
2 + -1x + 3xy + 9y = -2 + -9y + 2 + 9y

Reorder the terms:
2 + -1x + 3xy + 9y = -2 + 2 + -9y + 9y

Combine like terms: -2 + 2 = 0
2 + -1x + 3xy + 9y = 0 + -9y + 9y
2 + -1x + 3xy + 9y = -9y + 9y

Combine like terms: -9y + 9y = 0
2 + -1x + 3xy + 9y = 0

The solution to this equation could not be determined.

See similar equations:

| 4x^2+8x-4=100 | | log(10)x=0.6 | | -3x^2=-7x+12 | | 3x*y-x+9y+3=13 | | 3.1x-4=2.1x | | (2x^2+1x)+(6x+6)=0 | | ((2x^2)+1x)+(6x+6)=0 | | -3+(-3x)=18 | | 5+.50s=1s | | -5y+1(2)=5 | | -(2-8x)=3(8x-1)-16x+1 | | t(n)=-8-7(447) | | -3x-2(5y-7)=-12 | | -5+3x=3(x-6)+13 | | 180(n-2)=156 | | t(n)=14-3(447) | | 6w=8w-40 | | 1.04x/3.14=7.98 | | 19u-17u-u=20 | | 3x^3-x*y=5 | | x+6=x-4 | | ln8/ln4 | | ln8/lnr4 | | ln8/lv4 | | 9m+10-4m=-5 | | (5/9)x^2-(16/5)x-3/2=0 | | 10s-6s-3s-1=13 | | 3(8-x)-5=-6x-4+3n | | 3x-10+2x=-65 | | t(n)=-6+3(447-1) | | 4(6-9)/6= | | 8-(-4)2-5= |

Equations solver categories